The Impact of Green Transformational Leadership on Green Behavioral Intentions: Evidence from the Hospitality Industry - Alshimmari, Khawla Mohammad Omar; Shneikat, Belal (Journal of Posthumanism, 2025)
This study investigates the influence of Green Transformational Leadership (GTL) on Green Behavioral Intentions (GBI) within the UAE hospitality sector, focusing on high-end hotels. GTL integrates environmental consciousness into traditional leadership practices, inspiring employees toward sustainable behaviors. The study highlights GTL's role in driving GBI and Green Empowerment (GE), with Green Intrinsic Motivation (GIM) as a moderating factor. GE acts as a critical mediator, translating leadership strategies into actionable sustainability practices by fostering employee autonomy, ownership of green initiatives, and innovative commitment. Data collected from 281 employees in Dubai's 4 and 5 star hotels underscores GTL's significant impact on GBI and GE. GE was found to mediate the relationship between GTL and GBI. GIM moderates the relationship between GTL and dependent & mediator variables. GTL promotes a culture of environmental responsibility, enabling employees to align their behaviors with organizational sustainability objectives, such as waste reduction and energy conservation. Findings reveal that GE amplifies this relationship by empowering employees to take initiative, fostering creative solutions, and ensuring organizational commitment to sustainability goals. The study provides actionable insights for UAE hotels to align with national sustainability frameworks, including the UAE Vision 2030 and Dubai Clean Energy Strategy 2050. It recommends hotel leaders adopt GTL to cultivate an empowered and intrinsically motivated workforce, thus enhancing operational efficiency, environmental performance, and brand reputation. By emphasizing leadership's pivotal role, this research offers a pathway for the hospitality industry to contribute to global environmental goals and meet growing consumer demand for sustainable practices. The integration of GTL in organizational strategies represents a transformative approach to achieving long-term sustainability in the UAE hospitality sector.